Dengue associated with severe cutaneous leukocytoclastic vasculitis and pericardial effusion: a case report - da Costa, Laurisson Albuquerque (Rev Inst Med Trop Sao Paulo, 2020)
Dengue is a viral disease, caused by an arbovirus of the genus Flavivirus. In Brazil, its incidence rate is high with a broad clinical spectrum. This report discusses a rare case of dengue associated with cutaneous leukocytoclastic vasculitis and pericardial effusion with eminence of cardiac tamponade in a previously healthy patient with no comorbidities. The serology for dengue was positive and the histopathological analysis of the cutaneous lesions confirmed the diagnosis of leukocytoclastic vasculitis. After receiving treatment, the patient’s condition greatly improved.